Pengaruh Metode Demonstrasi Terhadap Minat dan Prestasi Belajar Siswa Kelas VII C Mata Pelajaran Fiqih di MTs Hidayatul Mubtadiin Jati Agung Lampung Selatan Tahun Pelajaran 2024/2025: Penelitian - Wulandari, Anisa; Sarpendi, Sarpendi; Latifah, Ami (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
At MTs Hidayatul Mubtadiin Jati Agung, particularly in class VIIc, many students are still less active in participating in Fiqh learning. This is due to the teacher not yet using effective methods that align with the material being taught, resulting in low student interest in learning and consequently low academic achievement. The purpose of this study is to determine the effect of the demonstration method on students' interest and academic achievement in Fiqh for class VIIc at MTs Hidayatul Mubtadiin Jati Agung, South Lampung. This research employs a quantitative approach with a post-test-only control group design, involving two groups in the sample. The population of this study consists of 67 students from class VII at MTs Hidayatul Mubtadiin. The sampling technique used is purposive sampling, with the sample taken from class VIIc, totaling 27 students. The data collection methods used in this study include questionnaires, observation, and documentation. The data analysis techniques employed involve prerequisite tests, including normality and homogeneity tests, as well as hypothesis testing. Based on the results of the t-test (partial) for learning interest, it shows that the calculated t-value (2.664) > t-table value (2.059), thus it can be concluded that Ha₁ is accepted and Ho₁ is rejected. Meanwhile, for learning achievement, the calculated t-value (2.803) > t-table value (2.059), indicating that Ha₂ is accepted and Ho₂ is rejected. Therefore, it can be concluded that there is an effect and a significant difference when using the demonstration method in increasing students' interest and academic achievement in the Fiqh subject at MTs Hidayatul Mubtadiin Jati Agung, South Lampung, in the 2024/2025 academic year.